Phylogeny and revision of Messatoporus Cushman (Hymenoptera, Ichneumonidae, Cryptinae), with descriptions of sixty five new species - Santos, Bernardo F.; Aguiar, Alexandre P. (Zootaxa, 2013)
The large New Worldgenus Messatoporus Cushman is diagnosed, redefined, described, and its species revised. A total of 89 valid species are recognized, of which 65 are described as new. All previously known species are redescribed and illustrated. The following synonyms are proposed: M. jocosus (Provancher) and M. rufiventris Cushman under M. discoidalis (Cresson), syn. nov. and M. tricolor (Szépligeti) under M. variegatus (Szépligeti) syn. nov. The following new species are proposed: M. advenus, M. albiaterartus, M. allomeros, M. amarelus, M. amazonensis, M. amplithorax, M. andinus, M. anepomius, M. apiopharkis, M. argentinus, M. atlanticus, M. atrifoveus, M. aurantius, M. badius, M. basiflavus, M. bennetii, M. bicolor, M. bimaculatus, M. campanulatus, M. caxiuanensis, M. citreocephalus, M. complexifemur, M. concavivenus, M. convexus, M. copiosus, M. depressifrons, M. dialeipsis, M. dissidens, M. dominicanus, M. elektor, M. ellipsicavus, M. euryoikos, M. igneus, M. interceptus, M. keraiopetalus, M. laevilatus, M. latissulcus, M. longicaudis, M. longitergus, M. lordos, M. lunatus, M. maculiscus, M. matucanus, M. nigriangulatus, M. nigriscapus, M. nigriscutus, M. occidentalis, M. opacus, M. orientalis, M. paeneater, M. pallidus, M. paradoxus, M. paralissonotus, M. pleuriflavus, M. semialbiventris, M. semiaurantigaster, M. subalaris, M. tenuiorbis, M. tenuissimus, M. teutonicus, M. titans, M. unidentatus, M. unimaculatus, M. versicolor and M. xanthogaster spp. nov. As well, a lectotype is designated for M. townesi Alayo and Tzankov, and Messatoporus nigrispina (Cameron) is transferred to Prosthoporus Porter, comb. nov.. A key to species based on both sexes is also presented, and new distribution records and distribution maps are provided. The validity and relationships of the genus are investigated cladistically using 162 morphological characters for 27 species of Messatoporus and 105 outgroup taxa. Tree search was conducted using TNT under implied weighting, with values of 1–6 for the concavity constant (K). All analyses recovered Messatoporus as a monophyletic group, supported by 7–11 synapomorphies. The results also support the monophyly of the six studied genera of Osprynchotina, in a clade including also Dotocryptus Brèthes. Messatoporus is diagnosed by the combination of the following features: apicolateral corners of clypeus projected; mandible long and tapered, ventral tooth much shorter than dorsal one or indistinct; transverse sulcus at base of propodeum long and shallow; anterior margin of propodeum concave; posterior area of propodeum almost always transversely wrinkled; first metasomal spiracle placed approximately on midlength; median dorsal carina of first metasomal segment absent; ovipositor basally cylindrical, apically depressed, with ventral valve enclosing completely dorsal valve as a sheath. A second analysis including all species of the genus was performed SANTOS & AGUIAR 4 · Zootaxa 3634 (1) © 2013 Magnolia Press to evaluate the phylogeny at the genus level. The character set for that analysis included 104 characters considered of phylogenetic importance within the genus, and used the same tree searching protocol as the first one. A distinct and gradual transition is detected, from species more similar to the remaining Osprynchotina to a significantly different morphotype with several convergences with the Gabuniina. These convergences are interpreted as adaptations to host location and substrate perforation, and may be related to use of more deeply concealed hosts.